Fertility perfomance of milk breed goats in Jaffna district - Navaratnarajah, A.; Nadesan, J. (My University, 2001)
An attempt was made to analyse the fertility performance of milk breed goats in Jaffna District of Sri Lanka. Anoetrus due to suckling and lactation caused delayed post-partum first oestrus. Farmers, mainly concerned in getting milk,breed the goats 5 to 6 months post-partum which resulted in lengthening of kidding to first service interval. Inefficient oestrus detection, inability to inseminate the does in proper time, faulty techiques of insemination, poor handling of semen and failure of early pregnancy diagnosis contributed for increase in services/Al per conception and prolonged interservices interval which could result in increased kidding to conception interval and thereby lengthening the kidding interval.